The link between individualism–collectivism and life satisfaction among emerging adults from four countries. Issue 2 (9th February 2021) - Germani, Alessandro; Delvecchio, Elisa; Li, Jian‐Bin; Lis, Adriana; Nartova‐Bochaver, Sofya K.; Vazsonyi, Alexander T.; Mazzeschi, Claudia
Abstract: The current investigation tested life satisfaction (LS), a cognitive component of subjective well‐being, among emerging adults, in the context of individualism (I) and collectivism (C), by distinguishing both cultural and individual levels of analysis, considering their horizontal (H) and vertical (V) dimensions, and controlling age and gender effects. Emerging adults ( N  = 1760 university students, aged 18–25, M age  = 19.46, SDag  = 1.50) located across four countries, namely China, Italy, Russia, and the USA, known to differ in the individualism index value (IDV), completed measures on the Horizontal and Vertical Individualism and Collectivism and Life Satisfaction. At the cultural level, an ANCOVA showed a significant country effects on LS. The post hoc comparisons indicated that the higher the country IDV score, the higher the average LS score, in the following order: Americans, Italians, Russians, and Chinese. At the individual level, LS was unrelated to HI and VI. Instead, it was associated with HC and VC. The positive link between LS and VC suggested an important role of family connectedness on LS across different cultures during emerging adulthood. However, contrary to previous studies, LS was unrelated to HI and VI.